King O' Fun - Hall, Justin; Singh, Anita (2004)
Colour Starring Andy Jones. Charlie Tomlinson (director), Robert Gautier & Geoff Younghusband (lighting & effects), Shelly Cornick & Paul Wade (set), Sean Panting (sound), Darka Erdelji (puppet sceneography), Anne Troake (movement coach), Cherie P Other